WAYS TO IMPROVE HUMAN RESOURCES MANAGEMENT SYSTEM - E. Kolesnichenko; Y. Kulikova; A. Berdikova (Вестник Северо-Кавказского федерального университета, 2022)
Human resources management has a specific impact on the processes offormation and formation ofpersonal potential of employees, guarantees its professional implementation, adaptation to the external and internal conditions of the production environment. The article considers the relevance of addressing the organization's human resource management problem, reveals the role of the leadership and human resources department in human resource management; The sources of attracting human resources at a specific enterprise are specified; reviewed the system of retaining specialists in the workplace of the enterprise; the human resources management system is analyzed. The most important, strategic role of human resources is to organize, interact and set in motion all the other resources of the enterprise, during which the greatest economic efficiency is achieved.